Swojskość i uniwersalizm – z wybranych zagadnień staropolskiego i oświeceniowego piśmiennictwa religijnego - Trościński, Grzegorz (Tematy i Konteksty, 2016)
Old Polish and Enlightenment religious literature is a fascinating area of research in past culture. It is still too early to claim comprehensive knowledge of it even though systematic work has been in progress for decades. The present issue of “Tematy i Konteksty” is the second collection of papers focused upon this current in old Polish literature. This issue is devoted to the relations of familiarity and universalism in Old Polish and Enlightenment religious literature. The main emphasis in the papers has been placed upon the Brest Bible and biblical inspirations, homiletics and occasional literature, religious drama, religious confession, mysticism, meditation, religious prints and manuscripts.